Immobilized-Ti₃C₂ interfacial ozone activation coupled with metastable Al-water for accelerated cyclophosphamide removal - Apiladda Pattanateeradetch; Chainarong Sakulthaew; Qingfeng Xu; Yao-Tung Lin; Zacharias Frontistis; Dionissios Mantzavinos; Chanat Chokejaroenrat (Journal of Environmental Chemical Engineering, 2026)

Phenolic acid-modified Arabic gum as an advanced functional stabilizer to enhance gelation and water retention of emulsion-type myofibrillar protein gels under oxidative stress - Tianhao Zhu; Mingze Xu; Yi Luan; Khubaib Ali; Peipei Yin; Qingling Wang; Rui Liu; Qingfeng Ge; Hai Yu; Mangang Wu (Food Hydrocolloids, 2026)

Macrocycle-size-modulated Cl− microenvironments in cationic mesoporous polymers for rapid capture of volatile iodine - Zhangjie Huang; Jinkai Qiu; Liang Liu; Qimeng Sun; Xiaoyong Xia; Cheng Lian; Dongyun Chen; Hua Li; Qingfeng Xu; Jianmei Lu (Chemical Engineering Journal, 2026)

Decoupled lake-glacier hydrological responses to Holocene climate forcing on the central Tibetan Plateau - Qiangqiang Kou; Liping Zhu; Teng Xu; Qingfeng Ma; Xiangjun Wu; Junbo Wang; Jianting Ju; Thorsten Bauersachs (CATENA, 2026)

Spatial and temporal evolution of the groundwater depth and indirect effects during the spring irrigation period in the Hetao Irrigation District - Yi Zhao; Haibin Shi; Xianyue Li; Shuya Yang; Haoqi Han; Yunlei Dong; Qingfeng Miao; Jianwen Yan; Cong Hou; Xu Dou (Irrigation Science, 2026)

miR-4632-5p Alleviates Lumbar Disc Degeneration by Targeting MAP3K11: A Novel Role in Mitigating Nucleus Pulposus Cell Degeneration - Xinfei Lan; Haiyan Xue; Mianlong Lin; Jinxiang Zhang; Qingfeng Zhang; Canhua Xu (Biochemical Genetics, 2026)

A star’s death by a thousand cuts: the runaway periodic eruptions of AT2023uqm - Yibo Wang; Tinggui Wang; Shifeng Huang; Jiazheng Zhu; Ning Jiang; Wenbin Lu; Rongfeng Shen; Shiyan Zhong; Dong Lai; Yi Yang; Xinwen Shu; Tianyu Xia; et al. (Science Bulletin, 2026)

External electronic effect enhances room-temperature phosphorescence and photochromism in organophosphine oxide - Zhuke Gong; Xiudan Song; Jianhui Sun; Ruotong Ma; Qingfeng Mu; Yuanting Guo; Xiaojun Zhang; Hui Xu (Science Bulletin, 2026)

Chlorine enrichment mechanisms in coals from the middle Jurassic of Northwestern China: Evidence from Cryo-SEM and geochemical analyses - Xinyi Xu; Wenfeng Wang; Qingfeng Lu; Wenlong Wang; Bofei Zhang (International Journal of Coal Geology, 2026)

Fish-gill-inspired hierarchical membranes with charge-repulsion-mediated ion-selective nanostructures for enhanced desalination performance - Yingxue Zhang; Wei Sun; Haoyu Jiang; Qiuxuan Zhou; Najun Li; Qingfeng Xu; Hua Li; Dongyun Chen; Jianmei Lu (Chemical Engineering Journal, 2026)

Inferring irrigation regimes and sunshine duration from the distribution and spectral characteristics of farmland microplastics - Hangzheng Zhao; Xu Han; Changming Cao; Ziyi Zan; Bo-Tao Zhang; Jiamin Wang; Qingfeng Tang; Weifeng Yue; Yan Liu (Environmental Pollution, 2026)

Microbial Community Structure, Rather Than Diversity, Predicts Plant Yield Under Global Change - Xu Xu; Jie Liu; Shicong Chen; Shanshan Liu; Menghui Dong; Qingfeng Xu; Peiyao Yang; Ting Sun; Longzheng Wang; Hemu Zhang; Yang Yang; Qirong Shen; et al. (Global Change Biology, 2026)
Under global change, terrestrial plants adjust their physiological metabolism alongside adaptive restructuring of rhizosphere microbial communities, yet the mechanistic links between plant phenotypic plasticity and microbial consortia remain unclear. Here, we conducted a meta‐analysis of 272 global‐change experimental comparisons and found that, among all global change factors examined, nitrogen addition exerted the strongest effects on both plant yield and microbial community assembly. Plant adaptive responses were more strongly associated with shifts in microbial community structure than with changes in alpha diversity. Microbial community structure reorganization was associated with increased soil carbon availability, whereas higher local microbial beta diversity constrained the magnitude of structural change. Based on a reanalysis of published amplicon sequencing datasets, we found that more stable and complex microbial networks, enriched with Proteobacteria and Actinobacteria, were associated with higher plant yield. These findings underscore plant‐microbe co‐adaptation under global change, highlighting microbial community structure as a key mediator linking soil environmental shifts to plant adaptive performance.

Insight into the quality and structural mechanism of wheat noodle fortified with broken rice flour - Yaxing Xie; Weijie Qi; Ruobing Jia; Shuang Xu; Jinghan Zhang; Jianjun Cheng; Qingfeng Ban (Food Research International, 2026)

Development of yttrium-copper oxide on Mxene surface for boron doped diamond electrodes of electrochemical treatment for antibiotic removal - Kitipong Poomipuen; Chanat Chokejaroenrat; Usuma Jermnak; Athaphon Angkaew; Peechanika Chopjitt; Khomson Satchasataporn; Yao-Tung Lin; QingFeng Xu; Chainarong Sakulthaew (Desalination, 2026)

SuFEx-enabled functional materials in environmental treatment, energy and data storage, biomedicine and organic synthesis and catalysis - Haibo Wan; Xinyi Deng; Daoyong Chen; Peng Wu; Qingfeng Xu; Jianmei Lu (Chemical Engineering Journal, 2026)

RURBAN-Map: A knowledge-guided framework for nationwide fine-scale urban-rural land use mapping in China - Qiqi Zhu; Dongyang Li; Longli Ran; Yiran Xu; Yong Zhang; Qingfeng Guan (Remote Sensing of Environment, 2026)

Modulation of postmortem glycolysis in pork by electrostatic field: Roles of pyruvate kinase and myofibrillar protein phosphorylation - Yuqian Xu; Dequan Zhang; Martine Schroyen; Xin Li; Qingfeng Yang; Chengli Hou (Food Chemistry, 2026)

Fabrication and physicochemical characterization of SPI-gallic acid-guar gum ternary complexes: Insights into covalent bonding and structural tunability - Mingze Xu; Chen Gu; Khubaib Ali; Peipei Yin; Chang Liu; Rui Sun; Rui Liu; Qingfeng Ge; Hai Yu; Mangang Wu (Food Chemistry, 2026)

High-performance, durable bamboo conductive macrofibers based triboelectric nanogenerator for stable harvesting water wave energy - Jiaqi Liao; Qingyu Meng; Wenwen Zhu; Wenhao Xu; Yang Peng; Shitao Shi; Zewei Ye; Chencong Liu; Qingfeng Sun; Xiaoping Shen (Chemical Engineering Journal, 2026)

A web-based intelligent computing application for critical elements in Chinese coals - Na Xu; Wenze Lin; Pengfei Li; Qingfeng Wang (Earth Science Informatics, 2026)

Multi-head attention driven aggregation-differentiation network for probabilistic groundwater depth forecasting and depth-stratified early warning: A multi-site efficient framework - Jing Xu; Siyuan Liu; Jinran Wu; Yuming Mo; Kun Wang; Qingfeng Ji; You-Gan Wang; Ling Li (Environmental Modelling & Software, 2026)

Study on fire design method for timber beams treated with surface plastering application - Lingzhu Chen; Xi Chen; Qingfeng Xu; Mingqian Wang; Yubing Leng; Fuwen Zhang (Engineering Structures, 2026)

Impact performance of assembled aluminum alloy-concrete-carbon steel double-skin tubular column - Wengang Xu; Jigang Zhang; Qingfeng Yan; Wenli Chen; Zaixian Chen; Wei Li; Yun Niu; Zhaolong Li (Ocean Engineering, 2026)

Effects of anthropogenic activities on soil microbial communities and greenhouse gas fluxes in coastal wetlands of the Yellow River Delta, China - Jingyu Sun; Xiaoya Xu; Zihao Wang; Kun Li; Chenmiao Liu; Chen Li; Zhengxi Cai; Xinkun Zhao; Xinyi Xu; Hongjie Di; Qingfeng Chen (Journal of Environmental Sciences, 2026)

Knowledge-data-model-driven multimodal few-shot learning for hyperspectral fine classification: Generalization across sensor, category and scene - Qiqi Zhu; Mingzhen Xu; Rui Ma; Longli Ran; Jiayao Xue; Qingfeng Guan (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Low-amplitude structural features in the Baode Block, Ordos basin, China: Quantitative indicators, formation mechanisms, and coalbed methane implications - Fengfeng Du; Yanbin Yao; Yongchen Li; Qingfeng Zhang; Xiaoxiao Sun; Qiang Xu (International Journal of Coal Geology, 2026)

Progestins as emerging contaminants in soil: An investigation on their pollution characteristics and ecological risks - Qianwen Jiao; Zhenzhen Xu; Yuzhen Liu; Yimin Li; Yifan Zhao; Qingfeng Chen; Xiaoyan Shen (Environmental Research, 2026)

Keratan sulfate revisited: UPLC–MS/MS-based quantitative profiling reveals structural heterogeneity and deficiency in ocular pathologies - Xinping Wang; Han Zhou; Xi Liang; Yue Li; Shimei Shen; Yuxin Li; Qingfeng Niu; Bi Ning Zhang; Shuying Xu; Guangli Yu; Guoyun Li (Carbohydrate Polymers, 2026)

Translational Approaches for Human Pharmacokinetics and Pharmacodynamics Prediction of Antibody-drug Conjugates: Bridging Complexity from Bench to Bedside - Wenhang Xu; Chaohsuan Pan; Qingfeng He; Xiao Zhu; Xiaoqiang Xiang (Current Pharmacology Reports, 2026)

Sulfonamides and their transformation products in the Yellow River Delta, China: Occurrences, source apportionment, and ecological risks - Yimin Li; Qianwen Jiao; Yifan Zhao; Qingyue Xiang; Hongping Wang; Zhenzhen Xu; Qingfeng Chen; Xiaoyan Shen (Environmental Pollution, 2026)

pH-dependent synergistic enhancement of U(VI) transport by phosphate and bentonite colloids - Yanhui Wang; Qi Tan; Yujie Hong; Jingli Xie; Qingfeng Tang; Zhiwei Niu; Duoqiang Pan; Wangsuo Wu; Zhen Xu (Journal of Hazardous Materials, 2026)

Macrocyclic Schiff-base covalent organic polymers with synergistic multi-sites for high-temperature iodine/methyl iodide capture - Liang Liu; Zhonglin Ma; Jiaqing Huang; Zhangjie Huang; Jiajia Li; Jinkai Qiu; Ying Zheng; Cheng Lian; Dongyun Chen; Long Chen; Qingfeng Xu; Jianmei Lu (Journal of Hazardous Materials, 2026)

Hybrid molecules with dual inhibition of acetylcholinesterase and tau hyperphosphorylation: design, inhibitory activity evaluation, apoptosis assessment, and mechanistic exploration - Qingfeng Hu; Kai Xu; Qingnian Ran; Wencheng Zhang; Changsheng Gan; Qunling Fang; Ailing Hui (Chemico-Biological Interactions, 2026)

Cost-minimizing alternative dosage regimens of imipenem/cilastatin/relebactam for patients with renal impairment: a pharmacokinetic/pharmacodynamic simulation study - Xiaoping Shi; Donghui Lao; Qing Xu; Xiaoyu Li; Bijue Liu; Qingfeng He; Xiao Zhu; Qianzhou Lv (European Journal of Clinical Pharmacology, 2026)

Effect of coating pretreatment on sensory quality of vacuum low temperature fried crisp jujube - Ruizhu Wang; Mingqiang Xu; Qingfeng Han; Yunpeng Liu; Kai Chen (International Journal of Gastronomy and Food Science, 2025)

Variable-intensity electrostatic fields inhibit specific spoilage organisms in fresh meat: Mechanisms and antimicrobial efficacy - Su Wang; Debao Wang; Xiangyuan Wen; Yuqian Xu; Dongmei Leng; Qingfeng Yang; Chengli Hou; Xin Li; Dequan Zhang (Food Chemistry, 2025)

Unraveling Eu(III) immobilization and cotransport risk with Bacillus subtilis from colloid aggregation, biosorption, and biomineralization - Zhen Xu; Qingfeng Tang; Yanhui Wang; Yuan Chen; Zhiwei Niu; Duoqiang Pan; Wangsuo Wu (Chemical Engineering Journal, 2025)

Study on the Influence of Geological Fault Structure on the Energy Evolution of Rockbursts - Shoujian Peng; Chaolong Qin; Qingfeng Xu; Jiang Xu; Yan Yang; Feng Jiao; Xiaoli Nong; Ming Li (Rock Mechanics and Rock Engineering, 2025)

SuFEx-derived macrocyclic polysulfates for efficient dual capture of methyl iodide and iodine - Shuai Shi; Zhonglin Ma; Long Chen; Yuqi Zhang; Haibin Shi; Qingfeng Xu; Jianmei Lu (Chemical Engineering Journal, 2025)

Mechanistic insights into metformin's anti-hyperuricemic effect: Targeting PPP/DNPB/XOD-mediated purine pathway, purinosome assembly, and gut microbiota homostasis in rats - Qiuxia Yu; Huijun Liao; Wenwen Tan; Lieqiang Xu; Guoshu Lin; Zhixuan Ai; Qingfeng Xie; Yuhong Liu; Yucui Li; Xiaobo Yang; Ziren Su; Guo Ma; et al. (Chemico-Biological Interactions, 2025)

Triple-synergistic dual-macrocyclic polysulfates for efficient capture of diverse iodine species - Jiajia Li; Jiaqing Huang; Xiaoyong Xia; Liang Liu; Chunyue Xu; Jinkai Qiu; Cheng Lian; Qingfeng Xu; Jianmei Lu (Journal of Environmental Chemical Engineering, 2025)

Preparation of a high-strength, antibacterial, and biodegradable bio-based film through amide crosslinking and nano-reinforcement for fruit packaging - Shuguang Yang; Yile Xu; Anbo Pan; Peisheng Li; Wenwu Yang; Qingfeng Sun; Xiaochun Zhang; Yantao Xu (Chemical Engineering Journal, 2025)

Bacillus subtilis morphology and bentonite colloids govern Eu(III) transport in quartz sand: Mechanisms and machine learning insights - Qingfeng Tang; Zhengye Feng; Yanhui Wang; Xiaoyan Wei; Duoqiang Pan; Wangsuo Wu; Zhen Xu (Journal of Hazardous Materials, 2025)

A triazine-tri-imidazole based cationic covalent organic polymer featuring high recyclability and radiation tolerance for efficient Re(Tc)O4- sequestration - Jiaqing Huang; Xiaoyong Xia; Jiajia Li; Liang Liu; Chunyue Xu; Jinkai Qiu; Cheng Lian; Qingfeng Xu; Jianmei Lu (Journal of Hazardous Materials, 2025)

Multi-factor analysis of enzyme activities under anthropogenic influence in the coastal wetland of the Yellow River Delta, China - Jingyu Sun; Xiaoya Xu; Xinkun Zhao; Qingfeng Chen (Journal of Environmental Management, 2025)

Occurrence, distribution, and potential risk of 61 glucocorticoids in soils in Shandong Province, China - Qianwen Jiao; Yifan Zhao; Yimin Li; Yuzhen Liu; Hongping Wang; Zhenzhen Xu; Qingfeng Chen; Xiaoyan Shen (Environmental Pollution, 2025)

Thiazolyl-conjugated porous polymer-coated CdZnS for synergistic adsorption and photocatalytic degradation of bisphenol A and with enhanced H2O2 production - Wanjun Xu; Yingxue Zhang; Shihong Dong; A.S. Gubin; I.N. Pugacheva; Najun Li; Qingfeng Xu; Hua Li; Dongyun Chen; Jianmei Lu (Chemical Engineering Journal, 2025)

Electrospinning-mist polymerized antibacterial and super-hydrophilic nanofiber membrane for efficient dust filtration and enhanced comfort in mines - Gang Zhou; Liwei Jiang; Bo Wei; Pengjin Liu; Jiafa Du; Tingting Fan; Song Xin; Rulin Liu; Qingfeng Xu; Seeram Ramakrishna (Chemical Engineering Journal, 2025)

Assessment of the immune-developmental toxicity risk of the hygienic insecticide dimefluthrin in zebrafish (Danio rerio) model - Ruirui Li; Yang Yu; Wenxuan Cheng; Qingfeng Li; Wenping Xu; Jiagao Cheng; Liming Tao; Yang Zhang (Journal of Environmental Management, 2025)

Vibration damping and finite element analysis of a 10 MW jacket-type offshore wind turbine - Jigang Zhang; Haodong Sui; Zhehao Ma; Wenli Chen; Qingfeng Yan; Wei Li; Hongjian Xu; Fengbo Yu; Yun Niu; Junxian Zhao (Ocean Engineering, 2025)

Solubility and mass transfer of hydrogen in light cycle oil and vacuum gas oil - Tao Jiang; Fei Yu; Hanfei Shen; Yan Yan; Qingfeng Tan; Chunming Xu; Zhentao Chen (Fuel, 2025)

Stretchable, controlled release of active substances, and biodegradable chitosan-polyvinyl alcohol hydrogel film for antibacterial and chilled meat preservation - Debao Wang; Chaoqiao Zhu; Qingfeng Yang; Yuqian Xu; Dequan Zhang; Daoying Wang; Fang Liu; Chengli Hou (Food Chemistry, 2025)

Predicting the Concentrations of Rare Earth Elements and Yttrium in Coal Using Self-Organizing Map - Na Xu; Fei Li; Wei Zhu; Mark A. Engle; Jiapei Kong; Pengfei Li; Qingfeng Wang; Lishan Shen; Robert B. Finkelman; Shifeng Dai (Natural Resources Research, 2025)

Knowledge graphs analysis for research on minerals in coal - Pengfei Li; Na Xu; Qingfeng Wang; Yuqing Wang; Fei Li; Wei Zhu; Qing Li (Earth Science Informatics, 2025)

Effects of anthropogenic activities on soil microbial community structure and methane anaerobic oxidation rate in coastal wetlands of Yellow River Delta, China - Chenmiao Liu; Zihao Wang; Xia Gao; Kun Li; Lei Yu; Jingyu Sun; Hongjie Di; Xiaoya Xu; Qingfeng Chen (Applied Soil Ecology, 2025)

The crucial role of protein corona in mediating the colloid stability and co-transport behaviors in saturated quartz columns - Zhen Xu; Qingfeng Tang; Qi Tan; Zhengye Feng; Yanhui Wang; Hui Zhang; Duoqiang Pan; Wangsuo Wu (Chemosphere, 2025)

Corrigendum to ‘What are exposure biomarkers of rare earth elements for the ionic rare earth occupational population?’ [Environ. Pollut. 345 (2024) 123499] - Qingfeng Chen; Jun Hong; Guowen Lai; Xiaobo Yang; Guoliang Chen; Na Xu; Xuewei Li; Kaibo Hu; Tianci Chen; Yang Song; Yinhua Wan (Environmental Pollution, 2025)

Toluene-induced framework expansion in carbazole-based porous organic polymers anchored with Cu-ZnIn2S4 for ultrafast azeotropic wastewater recovery - Yingxue Zhang; Xunxun Li; Wanjun Xu; Yuxin Cheng; Shihong Dong; Najun Li; Qingfeng Xu; Hua Li; Dongyun Chen; Jianmei Lu (Chemical Engineering Journal, 2025)

The Physical Simulation Study on Impact Damage Characteristics of Deep Elliptical Roadway - Qingfeng Xu; Shoujian Peng; Jiang Xu; Feng Jiao; Yan Yang; Chaolong Qin; Xiaoli Nong; Ming Li (Rock Mechanics and Rock Engineering, 2025)

Mechanistic model for the cotransport of colloids and radionuclides in saturated porous systems based on the interaction forces between colloids - Qi Tan; Qingfeng Tang; Xinyi Shi; Hongjie Zhao; Shuyang Li; Yuan Chen; Xiaoyan Wei; Zhen Xu; Duoqiang Pan; Wangsuo Wu (Applied Geochemistry, 2025)

Structural performance and design of assembled aluminum alloy-concrete-carbon steel double-skin tubular column - Wengang Xu; Jigang Zhang; Qingfeng Yan; Wei Li; Zhenhui Song; Fengbo Yu; Yun Niu; Hanyu Song (Ocean Engineering, 2025)

The hygienic insecticide dimefluthrin induced neurodevelopmental deficits and behavioral disorders in zebrafish (Danio rerio) larvae - Ruirui Li; Wenping Xu; Qingfeng Li; Jiagao Cheng; Zhong Li; Liming Tao; Yang Zhang (Environmental Research, 2025)

Intelligent identification of coal macerals using improved semi-supervised semantic segmentation methods - Na Xu; Qingfeng Wang; Pengfei Li; Jiapei Kong; Qing Li; Mark A. Engle; James C. Hower; Wei Zhu (International Journal of Coal Geology, 2025)

Fatty acid binding protein 4 regulates doxorubicin-induced renal injury via mediating lipid metabolism and apoptosis - Chuchu Wang; Tao Zhang; Yufeng Guan; Boye Han; Shang Wu; Xu Wang; Jing Yu; Junxia Zhang; Guoqiang Zhang; Qingfeng Miao; Suwen Su (Chemico-Biological Interactions, 2025)

Different ploidy-level hybrids derived from female common carp × male topmouth culter - Conghui Yang; Chenghua Dai; Qiong Liu; Yating Zhu; Xuexue Huang; Xiaowei Xu; Yi Zhou; Shi Wang; Qingfeng Liu; Shaojun Liu (Aquaculture, 2025)

The soil microclimate and microbial characteristics jointly drive the response of vegetation productivity to changes in snow cover — A global meta-analysis - Qingfeng Xu; Tianshan Zha; Peng Liu; Charles P.-A. Bourque; Xinhao Li (Science of The Total Environment, 2024)

Recognition of dispersed organic matter macerals using YOLOv5m model with convolutional block attention module - Yuanzhe Wu; Qingfeng Lu; Wenfeng Wang; Wenlong Wang; Jiaxin Li; Xinyi Xu; Kexin Che (Fuel, 2024)

Constructing local structure heterogeneity in AgNbO3-based antiferroelectrics: Achieving excellent anti-fatigue and energy storage properties - Shuaibing Gao; Zhihang Xu; Haolin Zeng; Meng Shen; Ye Zhu; Haitao Huang; Yongming Hu; Yunbin He; Qingfeng Zhang (Chemical Engineering Journal, 2024)

Study on Impact Tendency and Damage Characteristics of Rock-Like Materials Based on Acoustic and Thermal Responses - Shoujian Peng; Yan Yang; Qingfeng Xu; Jiang Xu; Chaolong Qin; Xiaoli Nong (Rock Mechanics and Rock Engineering, 2024)

Numerical Simulation of Self-Propelled Dive Motion of a Virtual Mooring Buoy - Hongyu Li; Huijie Cao; Jiayi Xu; Wenxin Li; Qingfeng Ma; Weizhuang Ma (Journal of Marine Science and Engineering, 2024)
To verify the feasibility of the variable wing actuator for a virtual mooring buoy, this paper investigates the self-propelled dive motion of a virtual mooring buoy under hydrostatic variable density conditions using a computational fluid dynamics (CFD) approach. The virtual mooring buoy developed by our research group is used in this study, and the numerical simulation is performed using the Reynolds-averaged Navier–Stokes (RANS) equation and the SST K-Omega turbulence model to capture the turbulent flow. Grid convergence studies were conducted at three grid resolutions to ensure the accuracy of the numerical simulations. The effects of different wing angles on the self-propelled dive motion of the buoy are focused on and analyzed. The results show that the maximum velocity of the buoy in the horizontal direction can reach 0.31 m/s, with a wing angle of −8°, which is about 35% higher than that of 0°, effectively enhancing the buoy’s anti-disturbance capability against the horizontal currents. In addition, this study further analyzes the self-propelled dive motion of the buoy with variable wing angles. The results show that the velocity and attitude of the buoy at any moment are basically the same as those under the corresponding fixed wing angle. This shows that it is possible to change the motion of the buoy by varying the wing angle, verifying the feasibility of the variable wing actuator.

Spatial-temporal characteristics of port infrastructures on sulfur-oxide concentrations of coastal port in China - Lang Xu; Jiyuan Wu; Qingfeng Zhao; Jihong Chen; Jutong Liu; Fangren Gao; Xiaorui Liu; Jianghao Xu (Ocean & Coastal Management, 2024)

Innovation of the global international ship registry system: Evolution process and future reforms - Jihong Chen; Jianghao Xu; Qingfeng Zhao; Zeng Yuan; Li Li; Huangziyi Chen; Yinuo Liu; Yuan Xiang (Ocean & Coastal Management, 2024)

Benzo(a)pyrene exposure impacts cerebrovascular development in zebrafish embryos and the antagonistic effect of berberine - Ke Xu; Qian Wang; Ying Zhang; Yuehong Huang; Qingfeng Liu; Meng Chen; Chonggang Wang (Science of The Total Environment, 2024)

Coupling low phosphorus fertilization with straw amendment highlights large crop productivity and reduced N2O emission in vegetable production - Zheng Zhao; Shuhang Wu; Haitao Zhu; Deping Zhou; Changbin Chu; Qingfeng Wang; Sixin Xu; Shumei Cai; Deshan Zhang (Applied Soil Ecology, 2024)

Cr(VI) behaves differently than Cr(III) in the uptake, translocation and detoxification in rice roots - Adeel Riaz; Yuan Qin; Qingfeng Zheng; Xuan Chen; Wei Jiang; Bisma Riaz; Nayun Xiao; Xiaojian Wu; Xianjin Qiu; Jianlong Xu; Guang Chen; Zhong-Hua Chen; et al. (Science of The Total Environment, 2024)

Engineering SuFEx-derived macrocyclic polysulfates for superior dynamic iodine capture at high temperatures - Shuai Shi; Zhonglin Ma; Haibo Wan; Long Chen; Qingfeng Xu; Jianmei Lu (Chemical Engineering Journal, 2024)

Distribution and transformation of potentially toxic elements in cracks under coal mining disturbance in farmland - Yin Lu; Xin Xiao; Yan Liang; Junchi Li; Chunying Guo; Lili Xu; Qingfeng Liu; Yu Xiao; Shiyuan Zhou (Environmental Geochemistry and Health, 2024)

Global daily mask use estimation in the pandemic and its post environmental health risks: Analysis based on a validated dynamic mathematical model - Ying Zhang; Fei Jiang; Fengmin Li; Shaoyong Lu; Zihao Liu; Yuwen Wang; Yiming Chi; Chenchen Jiang; Ling Zhang; Qingfeng Chen; Zhipeng He; Xiaoli Zhao; et al. (Journal of Hazardous Materials, 2024)

Inoculation fermentation with Lactobacillus fermentum L28 and Staphylococcus epidermidis S24 for improving the protein degradation of air-dried goose - Mangang Wu; Chen Gu; Likun Duan; Peipei Yin; Tianhao Zhu; Yuyu Xu; Qing Yin; Rui Liu; Qingfeng Ge; Hai Yu (Food Chemistry, 2024)

Late mid-Holocene cooling indicated by the Chibuzhang Co record in the central Tibetan Plateau - Qiangqiang Kou; Liping Zhu; Teng Xu; Qingfeng Ma; Junbo Wang; Jianting Ju; Hao Chen (Quaternary Science Reviews, 2024)

Millennial to orbital scale Indian summer monsoon evolution inferred from grain size end-members in Tengchongbeihai wetland, southwestern China - Dongliang Ning; Xiayun Xiao; Suqin Tang; Yuchen Xu; Xiang Kuai; Ying Ge; Jianan Zheng; Longjuan Cheng; Dejun Wan; Qingfeng Jiang; Yanling Li (Quaternary Science Reviews, 2024)

Effect of advance rate on excess pore water pressure induced by TBM tunnelling in saturated sand - Qingfeng Shi; Tao Xu; Dingwen Zhang (Computers and Geotechnics, 2024)

A biomass-enhanced bentonite slurry for shield tunnelling in the highly permeable soil - Tao Xu; Xiaoyu Wu; Jiaxin Liu; Qingfeng Shi; Jinquan Shi (Tunnelling and Underground Space Technology, 2024)

Grafting small organic molecules on donor-acceptor polymers to regulate electron push-pull interactions for efficient H2O2 production - Shuang Zhao; Najun Li; Qingfeng Xu; Hua Li; Jianmei Lu; Dongyun Chen (Chemical Engineering Journal, 2024)

A quaternary ammonium cyclodextrin polymer for efficient photocatalytic production of hydrogen peroxide from pure water - Bingshu Jiang; Dongyun Chen; Najun Li; Qingfeng Xu; Hua Li; Jianmei Lu (Chemical Engineering Journal, 2024)

Extracellular vesicles in plant-microbe interactions: Recent advances and future directions - Junsong Zhang; Liying Pan; Wenjie Xu; Hongchao Yang; Fuge He; Jianfeng Ma; Linlin Bai; Qingchen Zhang; Qingfeng Zhou; Hang Gao (Plant Science, 2024)

What are exposure biomarkers of rare earth elements for the ionic rare earth occupational population? - Qingfeng Chen; Jun Hong; Guowen Lai; Xiaobo Yang; Guoliang Chen; Na Xu; Xuewei Li; Kaibo Hu; Tianci Chen; Yang Song; Yinhua Wan (Environmental Pollution, 2024)

Estimation of the Relative Chlorophyll Content of Carya illinoensis Leaves Using Fractional Order Derivative of Leaf and Canopy Scale Hyperspectral Data - Jiajia Xu; Genshen Fu; Lipeng Yan; Lei Yu; Fan Kuang; Qingfeng Huang; Xuehai Tang (Journal of Soil Science and Plant Nutrition, 2024)
Chlorophyll is a crucial physiological and biochemical indicator that impacts plant photosynthesis, accumulation of photosynthetic products, and final yield. The measurement and analysis of chlorophyll content in plants can provide valuable insights into their nutritional status and overall health. The non-destructive and efficient estimation of relevant plant physiological and biochemical indicators using hyperspectral technology can provide a reliable method for collecting data on nutrient levels and health status during plant growth and development. Fifty-three Carya illinoensis plants of Jiande and Changlin series known for their exceptional qualities and significant economic benefits were used as the research object for collecting their leaf and canopy hyperspectral data. Firstly, fractional order derivative (FOD) was used for spectral preprocessing. Secondly, the spectral response relationship between spectrum and relative chlorophyll content (soil and plant analyzer development, SPAD) was explored by combining single-band and two-band spectral index (normalized difference spectral index, NDSI). The correlation coefficient of Pearson correlation analysis was used to estimate the linear correlation between variables. Finally, the correlation between the spectral feature variables and SPAD was analyzed and calculated. Top 10 absolute values of the correlation coefficients were screened out as modeling variables. eXtreme gradient boosting (XGBoost) machine learning algorithm was used to construct the optimal estimation model of SPAD of Carya illinoensis leaves. Results showed that the correlation between leaf and canopy spectrum after FOD pretreatment and SPAD was substantially improved, compared with raw spectrum. FOD combined with leaf and canopy NDSI was more effective than single band in improving the correlation between spectral characteristics and target components, which was increased by 0.166 and 0.338, respectively. The leaf spectrum could estimate SPAD more accurately than that of canopy spectrum. The optimal SPAD model was the 0.5th-order derivative transformation combined with two-band leaf spectral index (NDSI) model. The R 2 P was 0.788, and the RMSEP was 0.842 in prediction set. On one hand, this study confirms the feasibility of rapid and non-destructive estimation of SPAD of Carya illinoensis leaves using hyperspectral technology. On the other hand, FOD combined with two-band spectral indices can significantly improve the response relationship between spectral characteristics and target variables, enrich hyperspectral data processing methods, and propose a novel approach for the detection of plant nutrient level and health.

Metagenomic insights into the diversity of 2,4-dichlorophenol degraders and the cooperation patterns in a bacterial consortium - Shunli Hu; Chuangchuang Xu; Yanghe Xie; Lu Ma; Qingfeng Niu; Guomin Han; Junwei Huang (Science of The Total Environment, 2024)

Environmental-friendly enzyme nanoreactors with high adsorption capacity for long-time and efficient treatment of pollutants under visible light irradiation - Shuting Huang; Dongyun Chen; Najun Li; Qingfeng Xu; Hua Li; Jianmei Lu (Chemical Engineering Journal, 2024)

Insight into Impact of Phosphate on the Cotransport and Corelease of Eu(III) with Bentonite Colloids in Saturated Quartz Columns - Qingfeng Tang; Zhen Xu; Qi Tan; Xingyi Shi; Wangsuo Wu; Duoqiang Pan (Journal of Hazardous Materials, 2024)

Diversification of faunal exploitation strategy and human-climate interaction in Southern China and Southeast Asia during the last deglaciation - Yongxiu Lu; Feng Gao; Yiren Wang; Minmin Ma; Aifeng Zhou; Ruiliang Liu; Hiroki Kikuchi; Lele Ren; Qingfeng Shao; Lin Chen; Yongxiang Xu; Haoran Li; et al. (Quaternary Science Reviews, 2023)

Graphene aerogel-doped CoFe2O4/MoS2 sheets for magnetic oil absorption and the degradation of contaminants - Xin Xiang; Wenxuan Deng; Zhiyi He; Dongyun Chen; Najun Li; Qingfeng Xu; Hua Li; Jianmei Lu (Journal of Environmental Chemical Engineering, 2023)

Enhanced VOCs adsorption and oxidation by hydrophobic-layer-modified YMn2O5 mullite catalyst with ultralow single-atom Pt loading - Jiaqin He; Yaru Wang; Xunxun Li; Jun Xiao; Yunchong Liu; Hua Li; Najun Li; Qingfeng Xu; Dongyun Chen; Jianmei Lu (Chemical Engineering Journal, 2023)

Distribution and transformation of potentially toxic elements in crack under coal mining disturbance - Junchi Li; Qinxue Yu; Ruoxi Qian; Xin Xiao; Yan Liang; Ping Luo; Hui Wang; Yin Lu; Lili Xu; Qingfeng Liu; Yu Xiao (Environmental Monitoring and Assessment, 2023)

Coupling of soil methane emissions at different depths under typical coastal wetland vegetation types - Kun Li; Zihao Wang; Qingyue Xiang; Xinkun Zhao; Linhui Ji; Yu Xin; Jingyu Sun; Chenmiao Liu; Xiaoyan Shen; Xiaoya Xu; Qingfeng Chen (Chemosphere, 2023)

Mechanistic insights into gel formation of egg-based yoghurt: The dynamic changes in physicochemical properties, microstructure, and intermolecular interactions during fermentation - Jianwei Zang; Xiaoyang Pan; Yuanyuan Zhang; Yonggang Tu; Haixia Xu; Daobang Tang; Qingfeng Zhang; Jiguang Chen; Zhongping Yin (Food Research International, 2023)

Interannual variation in gross ecosystem production and evapotranspiration in a temperate semiarid grassland undergoing vegetation recovery - Xinhao Li; Tianshan Zha; Peng Liu; Charles P.-A. Bourque; Xin Jia; Yun Tian; Chuan Jin; Xiaoshuai Wei; Xinyue Liu; Hongxian Zhao; Qingfeng Xu; Shaorong Hao (Agricultural and Forest Meteorology, 2023)

Boosted photogenerated charge carrier separation by synergy of oxygen and phosphorus co-doping of graphitic carbon nitride for efficient 2-chlorophenol photocatalytic degradation - Zhuzhu Zhang; Qimeng Sun; Rui Ji; Dongyun Chen; Najun Li; Hua Li; Qingfeng Xu; Huilong Dong; Jianmei Lu (Chemical Engineering Journal, 2023)

Pyrite and sulfur-coupled autotrophic denitrification system for efficient nitrate and phosphate removal - Xuzhen Liu; Changsheng Zhao; Tongtong Xu; Wei Liu; Qingfeng Chen; Luzhen Li; Yu Tan; Xiaokai Wang; Yanan Dong (Bioresource Technology, 2023)

Low-dose graphene oxide promotes tumor cells proliferation by activating PI3K-AKT-mTOR signaling via cellular membrane protein integrin αV - Zhiwen Zheng; Abuduliaizezi Halifu; Juan Ma; Leyi Liu; Qingfeng Fu; Bocun Yi; E. Du; Dawei Tian; Yong Xu; Zhihong Zhang; Jianqiang Zhu (Environmental Pollution, 2023)

Biomimetic porphyrin-modified 3D porous composite material adsorption enhances photocatalytic CO2 reduction and tetracycline oxidative degradation - Mengmeng Wang; Yingxue Zhang; Dongyun Chen; Najun Li; Qingfeng Xu; Hua Li; Jianmei Lu (Chemical Engineering Journal, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

Highly enhanced direct catalytic oxidation of cyclohexane to adipic acid with molecular oxygen: Dynamic collaboration between zeolite channel micro-environment and Au clusters - Zhiyang Zhang; Mi Hu; Qingfeng Gui; Jing Gu; Wenlong Xu; Qingbo Xiao; Wei Huang (Chemical Engineering Journal, 2023)

Study on time effect of acidified pulverized coal micro components and discussion on mathematical correlation of influencing factors - Qingfeng Xu; Shoujian Peng; Jiang Xu; Feng Jiao; Liang Cheng; Li Jia; Hailin Yang; Yan Yang; Rulin Liu; Seeram Ramakrishna (Fuel, 2023)

PneuNet: deep learning for COVID-19 pneumonia diagnosis on chest X-ray image analysis using Vision Transformer - Tianmu Wang; Zhenguo Nie; Ruijing Wang; Qingfeng Xu; Hongshi Huang; Handing Xu; Fugui Xie; Xin-Jun Liu (Medical & Biological Engineering & Computing, 2023)

Seismic event classification based on a two-step convolutional neural network - Long Yue; Junhao Qu; Shaohui Zhou; Bao’an Qu; Yanwei Zhang; Qingfeng Xu (Journal of Seismology, 2023)

Responses of Soil Humus Composition and Humic Acid Structural Characteristics to the Addition of Different Types of Biochar in Phaeozems - Qi Wang; Yingxue Zhu; Lianzhou Xu; Baiyang Chen; Chunzhu Liu; Xianfa Ma; Qingfeng Meng; Bing Liu; Zongwei Huang; Yusheng Jiao; Ye Yuan (Journal of Soil Science and Plant Nutrition, 2023)

Soil nitrogen content and key functional microorganisms influence the response of wetland anaerobic oxidation of methane to trivalent iron input - Zihao Wang; Kun Li; Feifei Yan; Qingyue Xiang; Xinkun Zhao; Linhui Ji; Yu Xin; Jingyu Sun; Chenmiao Liu; Xinyi Xu; Ying Zhang; Xiaoyan Shen; et al. (Chemosphere, 2023)

Methamphetamine induces cardiomyopathy through GATA4/NF-κB/SASP axis-mediated cellular senescence - Xu Zhao; Jiancong Lu; Cui Zhang; Chuanxiang Chen; Manting Zhang; Jingyi Zhang; Qingfeng Du; Huijun Wang (Toxicology and Applied Pharmacology, 2023)

Clinical manifestations of COVID-19 infection in dialysis patients and protective effect of COVID-19 vaccine - Xuehan Zhang; Qingfeng Chen; Gaosi Xu (Inflammation Research, 2023)

Enhanced remediation of phenanthrene in water and soil by novel biochar-immobilized bacterial microspheres - Kai Wang; Yang Sun; Dongyun Chen; Qingfeng Xu; Najun Li; Hua Li; Jianmei Lu (Chemical Engineering Journal, 2023)

Association of biomass fuel use with the risk of vision impairment among Chinese older adults: a cohort study - Ying Zhou; Minzhi Xu; Pan Ke; Hongkun Di; Yong Gan; Jing Feng; Xin Meng; Cheng Su; Qingfeng Tian; Zuxun Lu (Environmental Science and Pollution Research, 2023)

Long non-coding RNA UCA1 regulates MPP+-induced neuronal damage through the miR-671-5p/KPNA4 pathway in SK-N-SH cells - Zhengheng Hao; Wen Dang; Qingfeng Zhu; Jianxing Xu (Metabolic Brain Disease, 2023)

Preparation of N-doped cellulose-based hydrothermal carbon using a two-step hydrothermal induction assembly method for the efficient removal of Cr(VI) from wastewater - Xinkun Zhao; Hongxu Liang; Zihao Wang; Daijia Li; Xiaoyan Shen; Xiaoya Xu; Kun Li; Qingyue Xiang; Yihan Wu; Qingfeng Chen (Environmental Research, 2023)

Ni-Mn spinel aerogel catalysts with adsorption induced superior activity for Low-Temperature toluene oxidation - Jiaqin He; Xunxun Li; Yaru Wang; Jun Xiao; Yunchong Liu; Hua Li; Najun Li; Qingfeng Xu; Jinghui He; Dongyun Chen; Jianmei Lu (Chemical Engineering Journal, 2023)

Z- scheme heterojunction of BiOI nanosheets grown in situ on NH2-UiO-66 crystals with rapid degradation of BPA in real water - Rui Ji; Zhuzhu Zhang; Lechen Tian; Liujun Jin; Qingfeng Xu; Jianmei Lu (Chemical Engineering Journal, 2023)

CeO2 modified carbon nanotube electrified membrane for the removal of antibiotics - Qingfeng Ma; Yongbao Chu; Xiaoyu Ni; Jingyi Zhang; Haoze Chen; Fei Xu; Yan Wang (Chemosphere, 2023)

Soil nitrogen substances and denitrifying communities regulate the anaerobic oxidation of methane in wetlands of Yellow River Delta, China - Zihao Wang; Kun Li; Xiaoyan Shen; Feifei Yan; Xinkun Zhao; Yu Xin; Linhui Ji; Qingyue Xiang; Xinyi Xu; Daijia Li; Junhao Ran; Xiaoya Xu; et al. (Science of The Total Environment, 2023)

An intelligent model for early kick detection based on cost-sensitive learning - Peng Chi; Li Qingfeng; Fu Jianhong; Yang Yun; Zhang Xiaomin; Su Yu; Xu Zhaoyang; Zhong Chengxu; Wu Pengcheng (Process Safety and Environmental Protection, 2023)

Low quantity of Pt loaded onto CeCoOx nanoboxes: Surface–rich reactive oxygen species for catalytic oxidation of toluene - Yunchong Liu; Xunxun Li; Dongyun Chen; Najun Li; Qingfeng Xu; Hua Li; Jinghui He; Jianmei Lu (Journal of Hazardous Materials, 2023)

Sulfonate-modified calixarene-based porous organic polymers for electrostatic enhancement and efficient rapid removal of cationic dyes in water - Lechen Tian; Shiyuan Zhou; Jiaojiao Zhao; Qingfeng Xu; Najun Li; Dongyun Chen; Hua Li; Jinghui He; Jianmei Lu (Journal of Hazardous Materials, 2023)

Lead-Free Cs3Bi2Br9 perovskite In-situ growth on 3D Flower-like g-C3N4 microspheres to improve photocatalytic performance - Bingke Xie; Dongyun Chen; Najun Li; Qingfeng Xu; Hua Li; Jianmei Lu (Chemical Engineering Journal, 2023)

Mechanism of molecules crosstalk and the critical role of jasmonic acid on triterpenoid synthesis in Cyclocarya Paliurus cells under Aspergillus niger elicitor - Meng Wang; Daobang Tang; Qiongqiong Xiong; Jiguang Chen; Xiaoxiang Xu; Qingfeng Zhang; Jingen Li; Xiangju Zhou; Zhongping Yin (Journal of Plant Biochemistry and Biotechnology, 2022)

Sediment Waves on the Western Slope of the Chukchi Rise (Arctic Ocean) and Their Implications for the Paleoenvironment - Qingfeng Hua; Guanbao Li; Qingjie Zhou; Shujiang Li; Tengfei Xu; Baohua Liu; Hongxia Chen (Journal of Marine Science and Engineering, 2022)
Based on multibeam bathymetric data and high-resolution shallow sub-bottom profiles acquired during China’s 10th Arctic Scientific Expedition Cruise in 2019, a sediment wave field was found on the western slope of the Chukchi Rise, in the Arctic Ocean. This sediment wave field developed on the lower slope with water depths of between 1200 m and 1800 m and stretched 15 km in the downslope direction. It comprised several parallel sediment waves, with wavelengths ranging from 700 m to 3400 m and wave heights from 12 m to 70 m. In the vertical direction, well-stratified deposits, tens of meters thick, were affected by sediment waves, which exhibit asymmetric waveforms and upslope migration trends. The morphological and seismostratigraphic characteristics of the sediment waves suggested their genesis as a result of the interaction between the bottom current and seafloor morphology, which was also supported by hydrographical data adjacent to the sediment wave field. It was infered that this bottom current was related to the Arctic Circumpolar Boundary Current, which many researchers suggest flows through the study area.

An improved hybrid bream derived from a hybrid lineage of Megalobrama amblycephala (♀)×Culter alburnus (♂) - Dingbin Gong; Min Tao; Lihui Xu; Fangzhou Hu; Zehong Wei; Shi Wang; Yude Wang; Qingfeng Liu; Chang Wu; Kaikun Luo; Chenchen Tang; Rong Zhou; et al. (Science China Life Sciences, 2022)

Holocene hydroclimate changes on the north‐eastern Tibetan Plateau inferred from geochemical records in Lake Gyaring - Dongliang Ning; Qingfeng Jiang; Ming Ji; Yuchen Xu; Xiang Kuai; Ying Ge; Wenwei Zhao (Journal of Quaternary Science, 2022)
The north‐eastern Tibetan Plateau (TP) is an ideal region for understanding the interaction between the Asian Summer Monsoon (ASM) and the Westerlies. Here we present a high‐resolution elemental record from Lake Gyaring in the source region of the Yellow River to investigate the paleo‐hydroclimate changes over the past ~10 ka. Our results show that lithogenic elements (Ti, Rb, Mn, Ti, Zn and Ni) increased while carbonate‐related elements (Ca, Sr and Mg) decreased up the core sediments, indicating that the effective moisture on the north‐eastern TP has steadily increased throughout the Holocene. This inference is also supported by the gradual augmentation and diminution of Rb/Sr and Ca/(Ti + Fe + Al) ratios, respectively. The persistent wetting trend on the north‐eastern TP inferred from our study disagrees with the Holocene pattern of the ASM but corresponds well with that of the Westerlies. This implies that the strengthening Westerlies since the Holocene might have played a more important role than monsoon circulation in controlling the hydroclimate changes on the north‐eastern TP. However, the significant increase in the mid‐Holocene might be related to the combined effects of the strengthened ASM and Westerlies. Ultimately, Northern Hemisphere solar insolation and the substantial remnant of ice sheets might have controlled Holocene moisture availability on the north‐eastern TP through their influence on the intensity of the Westerlies and ASM as well as Atlantic Ocean sea surface temperatures.

A Control Algorithm for Sea–Air Cooperative Observation Tasks Based on a Data-Driven Algorithm - Kai Hu; Xu Chen; Qingfeng Xia; Junlan Jin; Liguo Weng (Journal of Marine Science and Engineering, 2021)
There is tremendous demand for marine environmental observation, which requires the development of a multi-agent cooperative observation algorithm to guide Unmanned Surface Vehicles (USVs) and Unmanned Aerial Vehicles (UAVs) to observe isotherm data of the mesoscale vortex. The task include two steps: firstly, USVs search out the isotherm, navigate independently along the isotherm, and collect marine data; secondly, a UAV takes off, and in its one round trip, the UAV and USVs jointly perform the task of the UAV reading the observation data from USVs. In this paper, aiming at the first problem of the USV following the isotherm in an unknown environment, a data-driven Deep Deterministic Policy Gradient (DDPG) control algorithm is designed that allows USVs to navigate independently along isotherms in unknown environments. In addition, a hybrid cooperative control algorithm based on a multi-agent DDPG is adopted to solve the second problem, which enables USVs and a UAV to complete data reading tasks with the shortest flight distance of the UAV. The experimental simulation results show that the trained system can complete this tas, with good stability and accuracy.

Study on dynamic damage characteristics of coal under alternating hydraulic pressure - Qingfeng Xu; Yanbin Yu; Rulin Liu; Weimin Cheng; Haotian Yang (Bulletin of Engineering Geology and the Environment, 2021)

Serological characteristics of COVID-19 patients - Mi Zhou; Jing Zhong; Lei Bi; Pengcheng Shang; Yan Xing; Bo Wang; Jianlan He; Ying Xu; Tao Luo; Maohua Ma; Qingfeng Li (Infectious Diseases, 2020)

The chimeric genes in the hybrid lineage of Carassius auratus cuvieri (♀)×Carassius auratus red var. (♂) - Qingfeng Liu; Yanhua Qi; Qiuli Liang; Xiujuan Xu; Fangzhou Hu; Jing Wang; Jun Xiao; Shi Wang; Wuhui Li; Min Tao; Qinbo Qin; Rurong Zhao; et al. (Science China Life Sciences, 2018)

Risk assessment of flood disaster and forewarning model at different spatial-temporal scales - Jun Zhao; Juliang Jin; Jinchao Xu; Qizhong Guo; Qingfeng Hang; Yaqian Chen (Theoretical and Applied Climatology, 2018)

Water Resources Risk Assessment Model based on the Subjective and Objective Combination Weighting Methods - Jun Zhao; Juliang Jin; Jiezhong Zhu; Jinchao Xu; Qingfeng Hang; Yaqian Chen; Donghao Han (Water Resources Management, 2016)

Intranasal H102 Peptide-Loaded Liposomes for Brain Delivery to Treat Alzheimer’s Disease - Xiaoyao Zheng; Xiayan Shao; Chi Zhang; Yuanzhen Tan; Qingfeng Liu; Xu Wan; Qizhi Zhang; Shumei Xu; Xinguo Jiang (Pharmaceutical Research, 2015)

The Expression Patterns of Septin-9 After Traumatic Brain Injury in Rat Brain - Hui Mao; Jiao Liu; Wei Shi; Qingfeng Huang; Xide Xu; Lanchun Ni; Feihui Zou; Jinlong Shi; Debao Li; Yonghua Liu; Jian Chen (Journal of Molecular Neuroscience, 2013)

Roles of intracellular fibroblast growth factors in neural development and functions - Xu Zhang; Lan Bao; Liu Yang; QingFeng Wu; Shuai Li (Science China Life Sciences, 2012)